Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 101. Beitrag (Diptera: Sciaridae). - Menzel, Frank; Mohrig, Werner (Contributions to Entomology = Beiträge zur Entomologie, 1991)
In this contribution are listed all species of Sciaridae known from Albania. The material of the expedition of the DEI contains 59 specimens (18 species, 6 genera). Plastosciara (Plastosciara) friesei spec. nov. and Lycoriella (Bradysiopsis) rigua spec. nov. are described as new. In addition 14 species are recorded from Albania for the first time and 2 species are new for Europe. Considering the literature, now 32 species of Sciaridae from 9 genera are known from Albania. Nomenclatural Actsrigua Menzel & Mohrig, 1991 (Lycoriella (Bradysiopsis)), spec. n.friesei Menzel & Mohrig, 1991 (Plastosciara (Plastosciara)), spec. n.gracilipennis (Lengersdorf, 1942) (Scatopsciara), comb. n. hitherto Neosciara gracilipennis